The Association of Maternal Perceived Stress With Changes in Their Children’s Healthy Eating Index (HEI-2010) Scores Over Time - O’Connor, Sydney G (Ann Behav Med, 2019)
BACKGROUND: Few studies have examined the role of maternal stress in relation to their children’s dietary quality and its trajectory over time. PURPOSE: The objective of this longitudinal study was to examine the effect of baseline maternal stress on the change in their 8- to 12-year-old children’s dietary quality over 1 year. METHODS: Mother–child dyads (N = 189) from the greater Los Angeles area participating in the Mothers’ and their Children’s Health (MATCH) study in 2014–2016 completed assessments at baseline, 6 months, and 12 months. At baseline, mothers (mean age = 41.0 years, standard deviation [SD] = 6.1) completed the 10-item Cohen’s Perceived Stress Scale (PSS). At each time point, children (51% female, mean age = 9.6 years, SD = 0.9) completed up to two 24-hr dietary recalls. Dietary data were used to calculate each child’s Healthy Eating Index 2010 (HEI-2010) score at each time point. Multilevel models examined the effect of time on the patterns of change in children’s HEI-2010 scores over 1 year and the cross-level interaction between baseline maternal PSS score and time on the change in children’s HEI-2010 scores. RESULTS: On average, there was no significant linear change in child HEI-2010 across 1 year (b = −0.410, p = .586). Controlling for covariates, the rate of change in HEI-2010 differed depending on mother’s baseline PSS (i.e., significant cross-level interaction effect) (b = −0.235, p = .035). CONCLUSIONS: Our results showed that higher-than-average maternal stress at baseline was associated with greater decline in children’s dietary quality over 1 year. Family-based dietary interventions that incorporate maternal stress reduction could have positive effects on children’s dietary quality.